Advektive Pfade von Nährstoffen und ökologischen Schlüsselsubstanzen in der Arktis : Schlussbericht ... - Rabe, Benjamin; Vredenborg, Myriel; Schaffer, Janin; Schulz, Kirstin; Torres-Valdés, Sinhué; Heuzè, Cèline; Karcher, Michael; Sumata, Hiroshi ([Alfred-Wegener-Institute Helmholtz-Center for Polar and Marine Research], 2022)
Diagramme, Karten ... : https://creativecommons.org/licenses/by-nd/3.0/de/ ...